Spectrum of Fabricated Injuries Presenting in Lahore General Hospital, Lahore: Spectrum of Fabricated Injuries - Iqbal, Zubia; Asif, Muhammad; Maria, Gul; Mahmood, Khalid; Khan, Anwar; Asif, Huda (Pakistan Journal of Health Sciences, 2025)
Among the various types of injuries, fabricated injuries, those intentionally caused or exaggerated for personal gain, such as to facilitate insurance claims, commit criminal acts, or avoid legal consequences, present unique challenges in forensic analysis. Objectives: To identify, classify, and evaluate the various forms of fabricated injuries encountered in the forensic clinic of Lahore General Hospital, Lahore. Methods: A retrospective cross-sectional study was carried out at the Forensic Medicine and Toxicology Department of Lahore General Hospital, Lahore. Data were collected from medico-legal registers. The data included the number of individuals, age, sex, nature of injury and site of injury. From all medico-legal injuries, only fabricated injuries in individuals 18 years and above of both sexes were included in the study. SPSS version 25.0 was used for statistical analysis. Results: Male-dominated among all fabricated injuries across all age groups, comprising 83.63% (189/226) of total cases, while female made up 16.37% (37/226). The highest frequency of fabricated injuries was seen in the 21-25 years’ age group (21.97% total). Most of the male had sharp weapon injuries 100/113 (88.5%), and the scalp was the site bearing the maximum fabricated injuries with 51.3%. Female had blunter weapon injuries than sharp weapon injuries. Missing teeth due to blunt weapon dominated among all blunt force injuries. Conclusions: A holistic strategy is necessary to address the issue of fabricated injuries, which involves enhancing examiner qualifications, establishing uniform procedures, and promoting prompt and accurate reporting.